Search for decay of a fermiophobic Higgs boson h(f) -> gamma gamma with the D0 detector at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Prosper, H. B.; et al. (Amer Physical Soc, 2008)
We report the results of a search for a narrow resonance decaying into two photons in 1.1 fb(-1) of data collected by the D0 experiment at the Fermilab Tevatron Collider during the period 2002-2006. We find no evidence for such a resonance and set a lower limit on the mass of a fermiophobic Higgs boson of m(hf) > 100 GeV at the 95% C.L. This exclusion limit exceeds those obtained in previous searches at the Fermilab Tevatron and covers a significant region of the parameter space B(h(f) -> gamma gamma) vs m(hf) which was not accessible at the CERN Large Electron-Positron Collider.